Quality Management in the Public Sector: Definition and Prioritization of Indicators for Assessment and Decision-Making - Lelli, Valéria; Marinho, Fabiana Gomes; Mourão, Lucas Cabral Amador; Pamplona, Paulo Afonso; Almeida, Lucas Ferreira de; Andrade, Rossana M. de Castro; Santos, Ismayle de Sousa; Gurgel, Juliana Lopes; Silva, Maria Inês Vale (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
The use of historical data in software projects, when aligned with quality goals and business objectives, has increasingly been recognized as a strategic approach to enhancing both management and system development. This practice relies on the analysis of collected data, which enables the identification of opportunities and the anticipation of risks. As quality processes are implemented, these data are transformed into measures and metrics used to develop indicators, allowing for continuous performance monitoring and driving organizational improvement. In this context, this report presents the process used for the definition, validation, and prioritization of quality measures and indicators applied to the management and development of software projects in a public organization. Furthermore, in this study we discuss the main challenges faced, as well as the lessons learned and the benefits observed at the current stage of the process of implementing this practice within the institution.